Redress : debates informing exhibitions and acquisitions in selected South African public art galleries (1990-1994) - Cook, Shashi Chailey (Rhodes University, Faculty of Humanities, Department of Fine Art, 2009)
This thesis centres on the debates informing the progress of three public art galleries in South Africa between 1990 and 1994. This was a period of great change in the country, spanning from the unbanning of left-wing political parties and Nelson Mandela's release from prison, to the first democratic elections which resulted in his inauguration as President of South Africa. The study focuses specifically on the Johannesburg Art Gallery, the South African National Gallery, and the Durban Art Gallery, delineating the events and exhibitions held, the programmes initiated, and the artists represented by these galleries during this post-apartheid/pre-democracy phase of the country's history. The debates relevant to these galleries linked to those prevalent in the arts, museology, and politics at the time. Many contemporary South African artists called attention to apartheid oppression and human rights abuses during the 1980s. After 1990, with these pressures alleviating, there was a stage of uncertainty as to the role, responsibility, and focus of visual art in a post-'struggle' context, however there was also an unprecedented upswing in interest and investment in it. On a practical level, the administration of the arts was being re-evaluated and contested by both independent and politically-aligned arts groups. Public art museums and sponsored art competitions and exhibitions made increasing efforts to be 'representative' of South Africans of all races, cultures, creeds, sexes and genders. The many conferences, committees, and conventions created during this transitional era focused on the creation of policies that would assist in nation-building; historical and cultural redress and regeneration; and the education and representation of previously disadvantaged groups. This coincided with a revolution in museological discourses internationally, from the theorization of a museum as a place of commemoration and conservation, to a forum for discussion and revision between both academic and non-academic communities. With the sharing of the process of constructing history and knowledge, came the challenging dynamics involved in the representation of identity and history. In all of these groups - the arts, museology, and South African politics - the predominant issue seemed to be a negotiation between the bid to open up control to more parties, and the reluctance of some parties to relinquish control. While the emphasis is on significant changes that were implemented in the transitional period, the study locates the changes at the Johannesburg Art Gallery, the South African National Gallery and the Durban Art Gallery within their historical, geographical, and socio-political context. Various artists working in these locations during this era are also discussed, as the changes in their status, and the progressions in their subject matter, materials, and concerns are interesting to examine more nuanced definitions of the 'political', probing the politics of identity, sexuality, gender, race, geography, and belief systems. Some artists also focused specifically on post-apartheid preoccupations with territory, trauma, conflict, memory and freedom. This kind of artwork was assiduously acquired during the early '90s by public art galleries, whose exhibitions and collecting focus and policies were undergoing considerable revision and redress. This thesis examines these changes in light of their socio-political contexts, as well as in light of shifting national and international imperatives and conceptions of museums and museum practice.
Keywords: South African National Gallery Exhibition; Durban Art Gallery Exhibitions; Joahnnesburg Art Gallery Exhibitions; Art -- South Africa -- Exhibitions; Art, -- South African; Exhibitions -- South Africa; History; Exhibitions